IN VIVO ASSESSMENT OF POLYLACTIC CO-GLYCOLIC ACID NANOBUBBLES FOR TRIGGERED ENZALUTAMIDE DELIVERY: OPTIMIZATION, CHARACTERIZATION, AND DESIGN OF EXPERIMENTS-BASED EVALUATION - KUNDAVARAPU, NARENDRA; MAHALINGAM, KANNADASAN (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: This study aimed to develop and optimize polylactic co-glycolic acid (PLGA) nanobubbles (NBs) for the targeted and triggered delivery of enzalutamide (ENZ) using ultrasound-assisted activation. The formulation was designed to enhance drug bioavailability, prolong circulation time, and improve therapeutic efficacy while minimizing systemic side effects. Methods: ENZ-loaded PLGA NBs were synthesized using the solvent evaporation method, followed by optimization through the Box–Behnken design. The NBs were characterized for particle size (PS), polydispersity index (PdI), zeta potential (ZP), entrapment efficiency (EE), morphology, drug-excipient interactions, thermal stability, and crystallinity. In vitro drug release studies were conducted with and without ultrasound exposure. Pharmacokinetic evaluation was performed in vivo to assess systemic absorption, bioavailability, and drug retention. Results: The optimized ENZ-loaded NBs exhibited a PS of 193.5±2.8 nm, PdI of 0.261±0.016, ZP of 31.4±1.17 mV, and EE of 65.12±2.54%. Fourier-transform infrared, differential scanning calorimetry, and X-ray diffraction analyses confirmed successful drug encapsulation without significant chemical interaction. Scanning electronic microscopic analysis revealed uniform, spherical NBs. In vitro drug release studies demonstrated significantly enhanced drug release under ultrasound activation due to cavitation-induced NB disruption. Pharmacokinetic studies indicated that drug-loaded NBs achieved a significantly higher Cmax (1528.06±148.66 ng/mL) and area under the curve 0-∞ (65297.31±546.20 ng·h/mL) compared to the pure drug, with an extended half-life (43.07±3.13 h) and mean residence time (59.35±6.20 h), confirming improved bioavailability and sustained release. Conclusion: The study successfully formulated and optimized ultrasound-responsive PLGA NBs for ENZ delivery. The in vivo findings demonstrated enhanced systemic exposure and prolonged drug release, confirming the potential of NBs as an effective drug delivery system. These results highlight the feasibility of ultrasound-assisted NBs for targeted prostate cancer therapy, warranting further investigation into their clinical applications.